Efeitos do ensino sequencial e simultâneo de duas línguas estrangeiras na aquisição de um pequeno vocabulário em crianças - Cunha, Mariana Farias da (2024)
The present study investigated the effect of tact instruction (naming pictures) in two foreign languages (English and Spanish), conducted sequentially or simultaneously, on the emergence of bidirectional intraverbal responses (translation) between the two foreign languages (FL1 and FL2) and the native language (NL). Study 1 examined the effect of this instruction when conducted sequentially. Six children participated, three exposed to the FL1-FL2 sequence and three to the FL2-FL1 sequence. All participants were subjected to the following experimental conditions in a multiple baseline design: 1) Intraverbal Response Test (Pre-Instruction), which assessed bidirectional intraverbal responses (FL1-NL; NL-FL1; FL2-NL; NL-FL2; FL1-FL2; FL2-FL1); 2) Tact Test (pre-instruction), which assessed tact responses in the two foreign languages before exposure to the teaching condition; 3) Tact instruction, in which the experimenter presented each stimulus simultaneously with the question "What is this in English?" or "What is this in Spanish?" and then provided echoic prompts using progressive delay (0s; 2s; 4s) and provided differential reinforcement for responses; 4) Probes and Post-Instruction, which assessed the emergence of the six intraverbal relations tested after tact instruction; and 5) Maintenance, which assessed, after 30 days, the maintenance of directly taught tact relations and the six emerging intraverbal relations. In Study 1, there was no effect on the order of language instruction, but a learning set effect was observed in both orders, with high levels of emergence after instruction and during maintenance of taught and emerging relations. Study 2 aimed to investigate the effect of simultaneous tact instruction. Three children participated and were subjected to an adapted alternating treatment design and the same experimental conditions as Study 1. In Study 2, no differences were found in the amount of blocks for FL1 and FL2, and there were also varied levels of maintenance. Both studies were effective in producing emergence of bidirectional intraverbal relations, confirming results from previous studies. In both studies, participants demonstrated greater ease in responding in the native language and encountered more difficulties in relations between the foreign languages. Comparison between the studies should be done cautiously, as there was a relaxation of learning and emergence criteria for Study 2.